2016
DOI: 10.3390/ijgi5070105
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Land Cover Web Map Services from the Deep Web with JavaScript Invocation Rules

Abstract: Automatic discovery of isolated land cover web map services (LCWMSs) can potentially help in sharing land cover data. Currently, various search engine-based and crawler-based approaches have been developed for finding services dispersed throughout the surface web. In fact, with the prevalence of geospatial web applications, a considerable number of LCWMSs are hidden in JavaScript code, which belongs to the deep web. However, discovering LCWMSs from JavaScript code remains an open challenge. This paper aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Researchers have proposed various ways of overcoming this challenge. One approach is to enhance web crawler functionality so that it can discover geospatial metadata in geoportals [55,56] or enhance a search engine's capabilities for assessing the fitness of use of geospatial datasets [57]. Another approach is to include geospatial metadata in HTML pages, which are readily accessible by web crawlers [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have proposed various ways of overcoming this challenge. One approach is to enhance web crawler functionality so that it can discover geospatial metadata in geoportals [55,56] or enhance a search engine's capabilities for assessing the fitness of use of geospatial datasets [57]. Another approach is to include geospatial metadata in HTML pages, which are readily accessible by web crawlers [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others have proposed and developed special-purpose web crawlers that discover and understand geospatial resources in a geoportal [6,7], but this approach does not expose the resources for mainstream information retrieval. The research also contributes to online information retrieval generally by demonstrating the application of SEO techniques in the geospatial domain.…”
Section: Discussionmentioning
confidence: 99%
“…Such efforts are focused on enhancing the web crawler's capabilities to discover and understand geospatial resources in a geoportal [6,7]. They do not exploit the ability of such resources to make themselves visible to web search engines.…”
Section: Introductionmentioning
confidence: 99%
“…An ability to automatically generate standardized metadata from the content of a harvested data-publishing server would significantly facilitate maintenance and management of the description of large volumes of data as reported in previous research works (Florczyk et al, 2012;Kalantari et al, 2016;Giuliani et al, 2016). In addition, many research activities (Abargues et al, 2009;López-Pellicer et al, 2011;Kliment et al, 2013;Hou et al, 2016) have reported that the mainstream web provides significant number of valuable GI resources of several types (e.g. OGC services, KML data, etc.).…”
Section: State Of the Artmentioning
confidence: 93%